Legal Aspect Of The Right To Be Forgotten (RTF) On Social Media In Indonesia - Ramli, Ahmad M; Safiranita, Tasya; Olivia, Denindah; Millaudy, Reihan Ahmad (Technology and Economics Law Journal, 2022)
Social media as a digital platform has a highly specialized design. Firstly, the content distribution is massive and instantaneous; and secondly, all the information and contents contained in the social media are relatively permanent, almost eternal, and are easily accessible even though it has been for decades. Furthermore, it is becoming easier to find sources of information with a search engine, such as Google, that can display up to millions of search results in a fraction of a second. The guarantee of the right to privacy is, then, related to a new right that was first recognized on the European continent, namely the right to be forgotten which is part of the Privacy Right. Indonesia is the first country in the South East Asia to recognize the right to be forgotten.Meanwhile, Indonesia has provided a clear legal infrastructure to accommodate the enforcement of the right to be forgotten, namely, through regulation in Article 26 paragraph (3) of Law Number 19 of 2016 on the Amendments to Law Number 11 of 2008 on Electronic Information and Transactions. Aspects with regards to this right are also regulated in Article 16 - Article 18 of Government Regulation Number 71 of 2019 on the Implementation of Electronic Systems and Transactions. This article focuses on examining how the application of the right to be forgotten in the context of using social media in Indonesia.